Merchants without Borders: Quṣmân Traders in the Arabian Gulf and the Indian Ocean, c. 1850-1950 - Mansur al-Sharida (Arabian Humanities)
In order to map the network of al-Qaṣîm’s external trade and demonstrate the impact of their trade on both al-Qasim specifically and the whole region generally, this article follows the Qusmân traders’ economic activities in the Arabian Gulf and Indian Ocean during the second half of the 19th century and the first half of the 20th century. The paper finds that Quṣmân who migrated to the commercial centers of the Arabian Gulf and the Indian Ocean traded in anything available and profitable, such as slaves, horses, pearls, gold, currency, weapons, textile, carpets, dates, spice, rice, sugar, tea, coffee, and perfume. It concludes that since the Quṣmân could find foreign markets for al-Qaṣîm’s local products and brought in goods and foreign currency to their region, making al-Qaṣîm an entrepôt in Najd, their business demonstrated that Najd was incorporated into the global economy by the 19th century, if not even earlier.